The role of Islam in global inter religious dependence with particular reference to al-Faruqi - Ashimi, Tijani Ahmad (2013)
Islam is actually a religion of peace, tolerance and universal brotherhood; it is embodiment of the code of life which God the Creator and the Lord of the universe has revealed for the guidance of mankind. It is a unique religion in the sense that, it has related itself to most of the religions of the world (with particular reference to Judaism and Christianity), it does not deny truth to other religions, but says that later followers adulterated that truth by their own inventions, and that was a reason why God sent Prophet Muhammad (peace be upon him) to purify God’s religion. In fact, historically, Islam’s relation to other religions has been ideational. i.e linking the worldview of Islam, its view of God, of reality, of man of the world and history to the other religions. It is also practical. i.e. providing a modus vivendi for Muslims and adherent of other religions to live and work together, but each group according to the values and precepts of its own faith. Thus, this humble paper by looking at the work of Al- Faruqi , a gigantic scholar and energetic Muslim intellectual, will apply historical approach to demonstrate homogenous nature of Islam and its vis-a vis tolerance toward other religions, with particular reference to the respect that Islam gives to both Christianity and Judaism as part of Abrahamic faiths.